أحكام الصلح في قضايا شؤون الأسرة - العايب صالح (جامعة المسيلة, 2022)
تناولت الدراسة موضوع الصلح وأحكامه في قضايا شؤون الأسرة لإبراز مفاهيم الصلح في الفقه الاسلامي والقانون الجزائري ودوره في تسوية النزاعات الأسرية لحماية الأسرة والمجتمع حيث تناول البحث تعريف الصلح ومشروعيته وأهميته وأحكامه وإجراءاته وأثاره وتكمن أهميه الدراسة في بيان المعنى الحقيقي للصلح ومدى قدرته على انهاء النزاعات والخصومات في الحاضر والمستقبل بين أركان الرابطه الزوجيه وهما الزوج والزوجة فالصلح الحقيقي تسكن إليه النفوس وتزول به الأحقاد و الخلافات الماضيه فهو عمل فاضل حث عليه الاسلام لإشاعة السكينه والأمن وحماية الاسرة التي هي الخلية الأساسية لتكوين المجتمع والشريعة الاسلامية أجازته كطريق لإنهاء الخصومة وجعله المشرع اجراء قضائيا إجباريا على قاضي شؤون الأسرة من خلال الماده 49 من قانون الأسرة الجزائري وفي الأخير قدمنا بعض الاقتراحات لتفعيل الصلح وإعطائه دورا أكبر للوصول لنتائج أفضل أمام القضاء كلمات مفتاحيه : أحكام الصلح , قضايا , الإجراءات , حماية الأسرة Research Summary: The study dealt with the subject of conciliation and its provisions in family affairs issues to highlight the concept of reconciliation in Islamic jurisprudence and Algerian law and its role in settling family disputes to protect the family and society. The research dealt with the definition of conciliation, its legitimacy, importance, provisions, procedures and effects. The importance of the study lies in clarifying the right meaning of conciliation and its ability to end conflicts and disputes in the present and the future between the pillars of the marital bond, namely the husband and wife. The real conciliation calmed down the souls and removed the past grudges and disagreements. It is a virtuous act urged by Islam to spread peace and security and protect the family, which is the basic cell for the formation of society. Islamic law authorized it as a way to end the rivalry. The legislator made it a compulsory judicial procedure for the family affairs judge through Article 49 of the Algerian Family Code. In the end, we presented some suggestions to activate the conciliation and give it a greater role to reach better results in the judiciary. Keywords: conciliation provisions, issues, procedures, family protection.
Keywords: : أحكام الصلح , قضايا , الإجراءات , حماية الأسرة